CERTIFICATION OF IT COMPANIES' OWN PERSONNEL AND USERS OF THEIR SOFTWARE - PETRENKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the urgent problem of ensuring the uninterrupted professional development of IT company workers by introducing certification programs for experienced personnel and software security managers. It shows that current knowledge and information in various sectors of the economy complicate the management of business processes, especially in human resource management. Personnel certification is essential for improving workers' qualifications, motivation, and performance assessment.The research focuses on classifying software platforms, ERP, CRM, scientific data, analytics, e-commerce, financial technologies, and communication platforms. It analyzes the advantages and shortcomings of existing platforms for IT companies and their clients and emphasizes the importance of flexibility and scale for meeting clients' complex needs.Particular attention is paid to creating power platforms: priming, system type selection, development stages, testing, and deployment. In addition, a business process for certifying software developers is in place, which includes basic knowledge, practical tasks, testing, and evaluation of results. Recommendations were made to improve the economic efficiency of implementing the water supply system project for residents.Developing energy platforms and certification programs allows IT companies to ensure effective labor resource management, expand markets, and improve client relationships. Such approaches result in increased productivity, reduced costs for software product development, and enhanced worker qualifications.The results may be negative for local and international IT companies in developing strategies and corporate certification programs, and forming business processes directed to the effectiveness of client interactions.
Keywords: certification of workers; type of certification; IT company; personnel development; platform; CRM platform; ERP platform; business process